Novel modified nano-silica/polymer composite in water-based drilling fluids to plug shale pores. Issue 4 (21st December 2022) - Liu, Fei; Zheng, Zheng; Wang, Xiuying; Li, Xiaqing; Zhang, Zhaoxiang; Wang, Xuewu; Dai, Xiaodong; Xin, Yanping; Liu, Qingxue; Yao, Hailei; Jiang, Shunyao; Liu, Chao; et al.
ABSTRACT: The rapid growth of global energy demand necessitates high-performance water-based drilling fluids (WDFs) with excellent-plugging performance in the deep excavation of shale gas formation. Herein, we report an organic-inorganic nanocomposite (NS-D) as a plugging agent in WDFs to plug the nanoporous of shale and abate the hydration expansion of shale by integrating the advantages of inorganic and polymer nano plugging agents. The results of Fourier Transform infrared spectroscopy (FTIR) and proton nuclear magnetic resonance (H-NMR) revealed that NS-D had been successfully obtained. Additionally, thermogravimetric analysis (TGA) showed that the thermal degradation temperature of NS-D occurred after 354 °C. The results of plugging theory analysis showed that the presence of rich amide groups and rigid material silica not only made NS-D adhere to shale efficiently by hydrogen bonding, but also firmly blocked the nanoporous of shale. The plugging ability was evaluated by pressure transfer test and nitrogen adsorption test. The results showed that WDFs with NS-D can significantly improve plugging efficiency and reduce fluid invasion. On the other hand, NS-D sharply abated the fluid loss of WDFs due to its positive plugging performance. The filtrate volume of WDFs decreased by 90.5% and 88.3%, respectively, before and after hot rolling at 150°C for 16 h. Moreover, the plugging performance of NS-D for WDFs was significantly better than polymer plugging agent crosslinked polyacrylamide microspheres and inorganic plugging agent silica nanoparticles. This work provides a novel strategy to plug the nanoporous of shale in the process of shale gas exploration.